2019
DOI: 10.1021/acs.jnatprod.9b00121
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Metabolites of Onygenales Fungi Exemplified by Aioliomyces pyridodomos

Abstract: Fungi from Order Onygenales include human pathogens. Although secondary metabolites are critical for pathogenic interactions, relatively little is known about Onygenales compounds. Here, we use chemical and genetic methods on Aioliomyces pyridodomos, the first representative of a candidate new family within Onygenales. We isolated 14 new bioactive metabolites, nine of which are first disclosed here. Thirty-two specialized metabolite biosynthetic gene clusters (BGCs) were identified. BGCs were correlated to som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…From the predictions, only the BGCs for PKSs, NRPSs, siderophores, terpenes, homoserine lactones, and thiopeptides (as well as combinations of these biosynthetic enzyme families) were included in the succeeding analyses. An all-versus-all comparison of these BGCs was performed using Multi-GeneBlast (v1.1.14) (32) and a previously reported protocol (65). The bidirectional MultiGeneBlast BGC-to-BGC hits were considered to be reliable.…”
Section: Methodsmentioning
confidence: 99%
“…From the predictions, only the BGCs for PKSs, NRPSs, siderophores, terpenes, homoserine lactones, and thiopeptides (as well as combinations of these biosynthetic enzyme families) were included in the succeeding analyses. An all-versus-all comparison of these BGCs was performed using Multi-GeneBlast (v1.1.14) (32) and a previously reported protocol (65). The bidirectional MultiGeneBlast BGC-to-BGC hits were considered to be reliable.…”
Section: Methodsmentioning
confidence: 99%
“…The HRESIMS data indicated that the molecular formula of onygenaleoside D (4) was C 48 H 82 N 2 O 15 . In a comparison of the NMR data of 4 (Table 2) with 3 (Table 1), the 1 H and 13 Onygenaleoside E ( 5) was obtained as a white powder and afforded the molecular formula C 38 H 65 NO 10 based on its HRESIMS data. A comparison of the molecular weight and NMR data (Table 1 and Table 2 In addition to the six new compounds described above, another two known compounds were identified as malbrancheoside A (7) and malbrancheoside C (8).…”
Section: O-(2-n-acetylamide-α-d-glucopyranoside)-22-o-(2-n-acetyla-mentioning
confidence: 99%
“…11 Furthermore, these fungi have been found to be taxonomically close to human and animal pathogenic fungi. 12 Previous chemical investigations on the fungi of the family Onygenaceae have led to the isolation of polycyclic ether terpenoids, together with polyketides, 13 lignans, 14 and sesquiterpenes. 15 To further mine bioactive natural products with novel structures, a systematic investigation of the fungus Onygenales sp.…”
mentioning
confidence: 99%
“…The putative biosynthetic gene cluster was engineered into an Aspergillus nidulans expression host, enabling the isolation of varicidin A (77) with an MIC50 value of 8 μg/mL against C. Extended fermentation (365 days) of a marine-derived strain of Aioliomyces pyridodomos led to the appearance of new metabolites, of which onydecalin C (75) had an MIC of 2 µg/mL against Histoplasma capsulatum [63]. The same strain, in a more conventional fermentation period (25 days), produced aintennol A (76) with an IC 50 of 8 µg/mL against H. capsulatum [64]. Genome mining for potential Diels-Alderase enzymes identified a potential candidate in the genome sequence of Penicillium variabile.…”
Section: Natural Product Antifungal Leads From Fungimentioning
confidence: 99%